Functional objective parameters which may discriminate patients with mild cognitive impairment from cognitively healthy individuals: a systematic review and meta-analysis using an instrumented kinematic assessment. - Fuentes-Abolafio, Iván José; Stubbs, Brendon; Pérez-Belmonte, Luis Miguel; Bernal-López, María Rosa; Gómez-Huelgas, Ricardo; Cuesta-Vargas, Antonio (Oxford University Press, 2021)
Background: a systematic review in 2015 showed kinematic gait and balance parameters which can discriminate patients with mild cognitive impairment (MCI) from cognitively healthy individuals. Objective: this systematic review and meta-analysis aims to summarise and synthesise the evidence published after the previous review about the functional objective parameters obtained by an instrumented kinematic assessment which could discriminate patients with MCI from cognitively healthy individuals, as well as to assess the level of evidence per outcome. Methods: major electronic databases were searched from inception to August 2019 for cross-sectional studies published after 2015 examining kinematic gait and balance parameters, which may discriminate patients with MCI from cognitively healthy individuals. Meta-analysis was carried out for each parameter reported in two or more studies. Results: Ten cross-sectional studies with a total of 1,405 patients with MCI and 2,277 cognitively healthy individuals were included. Eight of the included studies reported a low risk of bias. Patients with MCI showed a slower gait speed than cognitively healthy individuals. Thus, single-task gait speed (d = -0.44, 95%CI [-0.60 to -0.28]; P < 0.001), gait speed at fast pace (d = -0.48, 95%CI [-0.72 to -0.24]; P < 0.001) and arithmetic dual-task gait speed (d = -1.20, 95%CI [-2.12 to -0.28]; P = 0.01) were the functional objective parameters which best discriminated both groups. Conclusion: the present review shows kinematic gait parameters which may discriminate patients with MCI from cognitively healthy individuals. Most of the included studies reported a low risk of bias, but the grading of recommendations assessment, development and evaluation criteria showed a low level of evidence per outcome.
https://openpolicyfinder.jisc.ac.uk/id/publication/1334
Keywords: Trastornos cognitivos; Cognitively healthy individuals; Functional objective parameters; Gait; Kinematic parameters; Mild cognitive impairment; Older adults